Trios for violin, viola, and cello, op. 9, published by Pleyel in 1799 - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Pleyel; Paris; France, 2023)
Three string trios (violin, viola, and cello) in G major, D major, and C minor, published by Pleyel in 1799 (address 724 reu Neuve-des-Petits Champs).